The seismic performance evaluation of unbonded laminated rubber bearings with end rotation. (May 2023) - Si, Mingfei; Wu, Yifeng; Xu, Hong; Li, Aiqun; Xu, Yubo; Lu, Song; Wang, Hao
Abstract: Laminated rubber bearing is a common quasi-isolation system in the small and medium span highway bridges in China, whose mechanical properties may change when the service disease occurs. Under such special supporting condition, the seismic performance evaluation of laminated rubber bearings becomes necessary. Therefore, compression shear tests and numerical simulation are conducted to investigate the effect of end rotation on the mechanical properties of unbonded laminated rubber bearings, in which eleven bearings are divided into B0, B1 and B2 groups. Experiment results show that the equivalent stiffness of bearings decreases with increasing end rotation angle, the maximum reduction ratio of B1s and B2s reaches 15.5% and 12.3% respectively; whereas the equivalent damping ratio exceeds 0.10 and varies slightly. Moreover, numerical results are in good agreement with testing ones, and the large end rotation angle will cause the yielding of steel shims according to the numerical results.